Interview to Dr Ana M. Bravo del Moral - Wendela Wapenaar (Universitat Politècnica de València, 2015)
Dr Wendela Wapenaar interviews Dr Ana M. Bravo del Moral, President of the European Association of Establishments for Veterinary Education (EAEVE).